2004
DOI: 10.1021/jo049260f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Pyridinolysis of S-4-Nitrophenyl 4-Substituted Thiobenzoates in Aqueous Ethanol

Abstract: The pyridinolysis of S-4-nitrophenyl 4-X-substituted thiobenzoates (X = H, Cl, and NO2; 1, 2, and 3, respectively) is studied kinetically in 44 wt % ethanol-water, at 25.0 degrees C and an ionic strength of 0.2 M (KCl). The reactions are measured spectrophotometrically (420-425 nm) by following the appearance of 4-nitrobenzenethiolate anion. Pseudo-first-order rate coefficients (kobsd) are obtained throughout, under excess of amine over the substrate. Plots of kobsd vs [free amine] at constant pH are linear wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…The p K a values for the phenols, SA amines, and pyridines were taken from 28–30. These p K a values were determined spectrophotometrically by the reported method 31.…”
Section: Methodsmentioning
confidence: 99%
“…The p K a values for the phenols, SA amines, and pyridines were taken from 28–30. These p K a values were determined spectrophotometrically by the reported method 31.…”
Section: Methodsmentioning
confidence: 99%
“…For the pyridinolysis of 2,4‐dinitophenyl X‐substituted benzoates (X=H, 4‐Cl, and 4‐NO 2 ) in 44 % aqueous ethanol, Castro et al demonstrated that the Brønsted‐type plot is downwardly curved for the reactions of unsubstituted benzoate, but linear for the corresponding reactions of 4‐chloro and 4‐nitro derivatives 10. More recently, the p${K{{0\hfill \atop {\rm a}\hfill}}}$ value has been reported to increase from 9.7 to 9.9 and >10 as the substituent X changes from H to 4‐Cl and 4‐NO 2 , respectively, for the pyridinolysis of ( S )‐4‐nitrophenyl X‐substituted thiobenzoates in 44 % aqueous ethanol 11. Thus, Castro et al concluded that the p${K{{0\hfill \atop {\rm a}\hfill}}}$ value increases as the substituent X in the nonleaving group is substituted for a stronger electron‐withdrawing group 11.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the p${K{{0\hfill \atop {\rm a}\hfill}}}$ value has been reported to increase from 9.7 to 9.9 and >10 as the substituent X changes from H to 4‐Cl and 4‐NO 2 , respectively, for the pyridinolysis of ( S )‐4‐nitrophenyl X‐substituted thiobenzoates in 44 % aqueous ethanol 11. Thus, Castro et al concluded that the p${K{{0\hfill \atop {\rm a}\hfill}}}$ value increases as the substituent X in the nonleaving group is substituted for a stronger electron‐withdrawing group 11. This argument is consistent with the conclusion drawn by Gresser and Jencks from reactions of diaryl carbonates with quinuclidines 12.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] For example, aminolyses of S-aryl-, [1] 4, S-aryl N-ethyl-, [2] 5, and p-nitrophenyl N-aryl carbamates, [3] 1, with benzylamines in acetonitrile were found to proceed by a concerted mechanism, while pyridinolyses of many aryl esters and carbonates are reported to proceed by a stepwise mechanism through a zwitterionic tetrahedral intermediate. [36][37][38][39][40][41][42][43] Anilines destabilize the tetrahedral intermediate relative to pyridines but stabilize it compared with benzylamines. The nucleofugality of anilines from T AE being intermediate between the two extremes, mechanistic changes can occur readily when Table 3.…”
Section: Resultsmentioning
confidence: 99%